La empresa petrolera Occidental-Oxy como un agente de desarrollo en la Amazonía ecuatoriana, su accionar e impactos para la nacionalidad Siekopaai - Payaguaje Payaguaje, Hernán Holger (2016)
The social, cultural and economic development of ancestral groups in the Amazon basin should be based mainly on their traditional knowledge to assure their sovereignty and the persistence of their culture. In present times, however, the development of most of these ancestral groups has been influenced by criteria created under a framework of a hegemonic, capitalistic model from the western civilization. In this context, this essay analyses the impact that the US oil company OCCIDENTAL–OXY (OEPC), in particular its Program of Social Compensation, had on the territory and lifestyle of the Siekopaai nation during the phases of oil exploration and extraction. The main aim of this work is to provide information and knowledge for the leaders and members of the Siekopaai nation that could help them in decision-making processes related to the presence of extractive industries in their territory, and as a tool for the conservation of the Siekopaai culture and environment.